Seasonal variations of blood aspartate aminotransferase and vitamin c on local breeds and cross breeds of sheep in konya central animal research institute - İbrahim Durmuş; Leyla Kalaycıoğlu (Eurasian Journal of Veterinary Sciences)
Fifty four sheep of Merino, Akkaraman, German Black Head (GBH) x Merino, GBHx Akkaraman, GBH x Ivesi, Hampshire Down (HS) x Merino, HSx Akkaraman, HS x Ivesi, Lincoln x Merino breed belonging Konya Central Animal Research Institute were used to determine the blood levels of activity of aspartate amino transferase (AST) and ascorbic acid during different seasons. Plasma AST activities changed between 76.53 and 102.48 U/lt during four seasons on the experimental animals. Plasma AST activities at different breeds was statistically different (P<0.05). Akkaraman sheep had the lowest activity as 76.53 U/lt and the Merino sheep had the highest activity as 102.48 U/lt. The season effected of the levels of plasma AST activities only at HS crosses. This effect was determined as the highest levels at winter and summer. The mean ascorbic acid levels at four seasons of nine sheep breed were 1.0211.438 mg/dl. The plasma ascorbic acid levels were significantly different at different breed groups (P<0.01) (Lowest at GBH x Merino, highest at HS x Ivesi). Seasonal variations of ascorbic acid levels were observed at all sheep groups except Merino and its crosses. At all groups examined the highest plasma ascorbic acid levels were at spring. The seasonal variations of the measured blood parameters suggest that the Merino crosses are resistant to Konya climate and the adaptation of HS crosses to this environment is difficult.